2013
DOI: 10.1088/0964-1726/22/3/035002
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and performance analysis of a DEA cuff designed for dry-suit applications

Abstract: A method for manufacturing a cylindrical dielectric elastomer actuator (DEA) is presented. The cylindrical DEA can be used in fabricating the cuff area of dry-suits where the garment is very tight and wearing the suit is difficult. When electrically actuated, the DEA expands radially and the suit can be worn more comfortably. In order to study the performance of the DEA, a customized testing setup was designed, and silicone-made cuff samples with different material stiffnesses were tested. Analytical and FEM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…An ideal active material candidate for integration into a wearable compression garment would meet the following criteria: 1) Can repeatably generate high forces and have the ability to produce large displacements when stimulated 2) Can be packaged or integrated into a textile structure easily and without adding significant bulk or mass 3) Can be stimulated in a way that is both feasible and safe for the wearer Given these requirements, many of the available active material candidates are currently ill-suited for the task (e.g., carbon nanotubes exhibit active strains of <1%, an impractically small activation stroke for the purpose of producing compression, and ferroelectric polymers often require bulky magnets) [12]. DEAs, SMPs, and SMAs all theoretically meet the minimum active stress requirements to achieve MCP design specifications (29.6 kPa) with at least single-digit active strains and form factors suitable for wearable systems [9], [10], [12], [15], [16]. Initial investigations into these materials suggest that DEAs and SMPs, in their current technical state, suffer from significant performance limitations: DEAs were shown to have very limited durability while requiring high (i.e., >1 kV) activation voltages [17], [18]; SMPs were shown to be deficient as they experience significant viscoelastic and irrecoverable strain effects [19].…”
Section: Introductionmentioning
confidence: 99%
“…An ideal active material candidate for integration into a wearable compression garment would meet the following criteria: 1) Can repeatably generate high forces and have the ability to produce large displacements when stimulated 2) Can be packaged or integrated into a textile structure easily and without adding significant bulk or mass 3) Can be stimulated in a way that is both feasible and safe for the wearer Given these requirements, many of the available active material candidates are currently ill-suited for the task (e.g., carbon nanotubes exhibit active strains of <1%, an impractically small activation stroke for the purpose of producing compression, and ferroelectric polymers often require bulky magnets) [12]. DEAs, SMPs, and SMAs all theoretically meet the minimum active stress requirements to achieve MCP design specifications (29.6 kPa) with at least single-digit active strains and form factors suitable for wearable systems [9], [10], [12], [15], [16]. Initial investigations into these materials suggest that DEAs and SMPs, in their current technical state, suffer from significant performance limitations: DEAs were shown to have very limited durability while requiring high (i.e., >1 kV) activation voltages [17], [18]; SMPs were shown to be deficient as they experience significant viscoelastic and irrecoverable strain effects [19].…”
Section: Introductionmentioning
confidence: 99%
“…The DC/DC converter is required to generate the high voltage that drives the DEA. Previous studies demonstrated that EMCO Q 101-5 works acceptably on robots made with DEAs (Wingert et al, 2006;Ahmadi et al, 2012;Shintake et al, 2015a). We set the maximum output to 3 kV because electrical breakdown within the DEAs occurred above this voltage.…”
Section: Controllermentioning
confidence: 99%
“…In this section, an analytical model of the cylindrical DEA [ 10 , 16 ] is combined to the model of the human calf described by ( 2 ). The total pressure applied by the ACB has two components, the mechanical pressure which is the pressure resulting from the mechanical stress in the ACB before actuating the ACB, and the actuation pressure, which is the pressure variation after actuating the ACB.…”
Section: Analytical Modeling Of the Dea On A Simulated Human Calfmentioning
confidence: 99%
“…As the stretch ratio of the ACB changes the amount of compression that is exerted on the calf is also changed. The amount of this compression is obtained using the following equation [ 16 ].…”
Section: Analytical Modeling Of the Dea On A Simulated Human Calfmentioning
confidence: 99%
See 1 more Smart Citation